N-terminal pro B-type natriuretic peptide and the risk of acute kidney injury after lung cancer surgery - Cagini, Lucio; Andolfi, Marco (Journal of Thoracic Disease; Vol 10, No 12 (December 30, 2018): Journal of Thoracic Disease, 2018)
As of recent, a growing attention is being paid to the importance of preoperatively evaluating patients prior to lung resection. Indeed, numerous studies have sought to identify reliable predictors of patients who are at a high risk of developing postoperative complications.